Impacts of Carbon Pricing in Reducing the Carbon Intensity of China's GDP - Cao, Jing; Ho, Mun; Timilsina, Govinda R. (World Bank, Washington, DC, 2016)
In contributing to global climate change mitigation efforts as agreed in Paris in 2015, China has set a target of reducing the carbon dioxide intensity of gross domestic product by 60-65 percent in 2030 compared with 2005 levels. Using a dynamic computable general equilibrium model of China, this study analyzes the economic and greenhouse gas impacts of meeting those targets through carbon pricing. The study finds that the trajectory of carbon prices to achieve the target depends on several factors, including how the carbon price changes over time and how carbon revenue is recycled to the economy. The study finds that carbon pricing that starts at a lower rate and gradually rises until it achieves the intensity target would be more efficient than a carbon price that remains constant over time. Using carbon revenue to cut existing distortionary taxes reduces the impact on the growth of gross domestic product relative to lump-sum redistribution. Recycling carbon revenue through subsidies to renewables and other low-carbon energy sources also can meet the targets, but the impact on the growth of gross domestic product is larger than with the other policies considered.